2022
DOI: 10.3390/ijerph19127498
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use and Exposure to Environmental Tobacco Smoke amongst Pregnant Women in the United Arab Emirates: The Mutaba’ah Study

Abstract: Self-reported tobacco use is high in the male adult Emirati population (males ~36% vs. females ~3%); however, there are minimal data on tobacco use or exposure to environmental tobacco smoke (ETS) during pregnancy in the United Arab Emirates (UAE). This study investigated the prevalence of, and factors associated with, tobacco use and exposure to environmental tobacco smoke (ETS) amongst pregnant women in the UAE. Baseline cross-sectional data were analysed from the Mutaba’ah Study. Expectant mothers completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The overall prevalence of active smoking during pregnancy reached as high as 9.2%, which is higher compared to studies carried out in other countries. A study in the Emirates found that the frequency of maternal smoking was as low as 0.7% (Taha et al, 2022). According to a study in Costa Rica, the rate of smoking among pregnant women was 2.7% (Quiñones et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall prevalence of active smoking during pregnancy reached as high as 9.2%, which is higher compared to studies carried out in other countries. A study in the Emirates found that the frequency of maternal smoking was as low as 0.7% (Taha et al, 2022). According to a study in Costa Rica, the rate of smoking among pregnant women was 2.7% (Quiñones et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that having an educational level of elementary school or lower carried lower odds of being exposed to smoke. A possible explanation for this may be that most other studies took into consideration the educational levels of both spouses (Taha et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations